Codevelopment of gut microbial metabolism and visual neural circuitry over human infancy - Kevin S. Bonham; Emma T. Margolis; Guilherme Fahur Bottino; Ana C. Sobrino; Fadheela Patel; Shelley McCann; Michal R. Zieff; Marlie Miles; Donna Herr; Lauren Davel; Cara Bosco; Curtis Huttenhower; et al. (mBio)
ABSTRACT Infancy is a time of elevated neuroplasticity supporting rapid brain and sensory development. The gut microbiome, also undergoing extensive developmental changes in early life, may influence brain development through the metabolism of neuroactive compounds. Here, we leverage longitudinal data from 194 South African infants across the first 18 months of life to show that microbial genes encoding enzymes that metabolize molecules playing a key role in modulating early neuroplasticity are associated with visual cortical neurodevelopment, measured by the Visual-Evoked Potential (VEP). Neuroactive compounds included neurotransmitters GABA and glutamate, the amino acid tryptophan, and short-chain fatty acids involved in myelination, including acetate and butyrate. Microbial gene sets around 4 months of age were strongly associated with the VEP from around 9–14 months of age and showed more associations than concurrently measured gene sets, suggesting that microbial metabolism in early life may affect subsequent neural plasticity and development.IMPORTANCEOver the past decade, extensive research has revealed strong links between the gut microbiome and the brain, at least in adults or those with neuropsychiatric disorders. This study explores how these associations emerge in early development using a longitudinal sample of 194 infants with repeated microbiome metabolism and electroencephalography (EEG) measures during the critical early period of visual cortex neuroplasticity. We examined microbial genes encoding enzymes for neuroactive compounds (e.g., GABA, glutamate, tryptophan, and short-chain fatty acids) and their association with the visual-evoked potential (VEP). Genes from 4-month stool samples strongly correlated with VEP features between 9 and 14 months, suggesting that early microbial metabolism influences later visual neurodevelopment. These prospective associations were more numerous than the concurrent ones. Our findings suggest that early gut microbiome metabolic potential plays a crucial role in shaping neural plasticity and visual neurodevelopment.